1999
DOI: 10.1021/bi990065i
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of the Human CC Chemokine 2:  A Monomeric Representative of the CC Chemokine Subtype,

Abstract: HCC-2, a 66-amino acid residue human CC chemokine, was reported to induce chemotaxis on monocytes, T-lymphocytes, and eosinophils. The three-dimensional structure of HCC-2 has been determined by 1 H nuclear magnetic resonance (NMR) spectroscopy and restrained molecular dynamics calculations on the basis of 871 experimental restraints. The structure is well-defined, exhibiting average root-mean-square deviations of 0.58 and 0.96 Å for the backbone heavy atoms and all heavy atoms of residues 5-63, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 60 publications
0
38
0
Order By: Relevance
“…For human CCL15 and CCL23, chemokines that share ϳ64% identity, the extra disulfide seems to have a negligible effect on structure. The extra disulfide in these two chemokines links a 3 10 -helical turn just before the first ␤-strand to the C-terminal ␣-helix and does not disrupt the conserved chemokine fold (17,19). In addition, mutational studies with CCL15 have shown that disruption of the extra disulfide has a minimal effect on protein structure (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For human CCL15 and CCL23, chemokines that share ϳ64% identity, the extra disulfide seems to have a negligible effect on structure. The extra disulfide in these two chemokines links a 3 10 -helical turn just before the first ␤-strand to the C-terminal ␣-helix and does not disrupt the conserved chemokine fold (17,19). In addition, mutational studies with CCL15 have shown that disruption of the extra disulfide has a minimal effect on protein structure (17).…”
Section: Discussionmentioning
confidence: 99%
“…The extra disulfide in these two chemokines links a 3 10 -helical turn just before the first ␤-strand to the C-terminal ␣-helix and does not disrupt the conserved chemokine fold (17,19). In addition, mutational studies with CCL15 have shown that disruption of the extra disulfide has a minimal effect on protein structure (17). However, structural studies on the chemokine CCL1 have shown that its extra disulfide bond significantly affects the conserved chemokine fold, resulting in disruption of the C-terminal ␣-helix and the formation of a short extended C-terminal strand not seen in other chemokines (16).…”
Section: Discussionmentioning
confidence: 99%
“…Many chemokines form homodimers or oligomers at high nanomolar to micromolar concentrations (36-39) whereas others exist strictly as monomers (40)(41)(42)(43)(44). For IL-8, MCP-1, MCP-2, and I-309, the monomeric form predominates in solution at physiological (nM) concentrations (32,44,45).…”
Section: Vv-35kda Protein Monomer Binds Monomeric Mcp-1mentioning
confidence: 99%
“…The various structurally characterized members of the family differ in their extent of oligomerization (monomers, dimers, and tetramers) and/or the surface used for the oligomerization interaction. [2][3][4] All the monomers, however, have a three-stranded ␤-sheet, followed by an ␣-helix and preceded by an extended N-terminal segment of approximately 20 amino acids. Four subclasses are currently discriminated on the basis of their pattern of cysteines near their N-terminus.…”
Section: Introductionmentioning
confidence: 99%